Systematic study of impacts of alkalis with SO3 on the hydration and microstructural development of oil well cement at medium temperatures - Hanhua Liu; Yang Li; Ying Ma; Dan Dai; Xiao Yao; Chunyu Wang (Case Studies in Construction Materials, 2025)
This work poses a systematic investigation of the impact of alkalis (KOH, NaOH) and sulfate (SO3) on oil well cement hydration, properties, and microstructure across temperatures (25–80 °C). The results reveal that alkalis accelerate early hydration, shortening induction periods and yielding earlier, higher heat peaks at 25 °C; this effect intensifies at 50 and 80 °C. NaOH accelerates more strongly than KOH. Alkalis reduce setting/thickening times by accelerating C3A hydration. Alkalis destabilize AFt, promoting conversion to AFm and hydrogarnet, especially at later ages and higher temperatures, while sufficient SO3 (3 %) stabilizes AFt. The effect of alkalis on compressive strength critically depends on SO3 content and temperature. Alkalis consistently reduce strength under low SO3 (1 %). Under 2–3 % SO3, they enhance early strength but generally reduce 28-day strength, except for an increase observed with alkalis under 3 % SO3 at 80 °C. A negative correlation exists between the Na2Oeq/SO3 molar ratio and 28-day strength at 25 and 50 °C. Although alkalis increase the degree of hydration (DoH), strength at a given DoH is lower, particularly with low SO3. Alkalis decrease the Ca/Si ratio in C-S-H and KOH promotes honeycomb-like C-S-H (II) with a lower Ca/Si ratio. Alkalis increase large capillary pores (>100 nm) and porosity at 25 °C (especially KOH with low SO3), contributing to strength loss. Alkalis also increase permeability regardless of SO3 or age, with KOH causing higher permeability. Strict alkali control and adequate gypsum are essential for safe oil well cement application.